It’s only fair: blood donors are more sensitive to violations of fairness norms than non-donors: converging psychometric and ultimatum game evidence - Ferguson, Eamonn; Lawrence, Claire (Wiley, 2018)
Background and Objectives: The design of effective donor recruitment campaigns requires an accurate understanding of donor motivations. This requires cross-validation of theoretically derived, psychometrically assessed motivations with behavioural preferences. Theoretical models suggest that blood donors should be more sensitive than non-donors to violations of fairness norms. Specifically, active blood donors, compared to non-donors, should endorse beliefs of reciprocal fairness, norms of both positive and negative reciprocity and reject more unfair offers in a behavioural economic game (the ultimatum game). The current study is the first to test this hypothesis.